Trouble Ticketing System Pada PT. Infokom Elektrindo Jakarta - Basuki Manto, Agung; - STMIK Nusa Mandiri, Rame Santoso (IJNS - Indonesian Journal on Networking and Security, 2017)
Abstract - PT. Infokom Elektrindo is a company engaged in telecommunications services VSAT. One of the largest telecommunications company in Indonesia which already has thousands of customers throughout Indonesia. The number of customers makes the company had to innovate in customer service handling problems that disturbance in customers can be served and handled quickly and effectively. One of the innovations that can be taken is Trouble Ticketing System. The system is able to improve the effectiveness and efficiency of work in handling customer issues. expected by the Trouble Ticketing System, customers will feel satisfied with the service company and can increase the number of customers who are satisfied with the service companies. Key Word : Decision Support System Abstraksi - PT. Infokom Elektrindo merupakan perusahaan yang bergerak dibidang jasa telekomunikasi VSAT. Salah satu perusahaan telekomunikasi terbesar di Indonesia yang sudah mempunyai ribuan pelanggan di seluruh Indonesia. Banyaknya pelanggan membuat perusahaan harus melakukan inovasi di layanan penanganan gangguan pelanggan agar gangguan yang terjadi di pelanggan dapat terlayani serta tertangani dengan cepat dan efektif. Salah satu inovasi yang bisa diambil adalah Trouble Ticketing System. Sistem yang mampu meningkatkan efektiftas dan efesiensi kerja dalam penanganan gangguan pelanggan. diharapkan dengan adanya Trouble Ticketing System ini, pelanggan akan merasa puas akan layanan perusahaan dan bisa menambah jumlah pelanggan yang merasa puas dengan layanan perusahaan. Kata Kunci : Pelanggan, Gangguan, Trouble Ticketing System, Puas.